Lifestyle and Consumerism in the Digital Era: Can Self-Control Be the Balancing Force? - Cahyaning Putri, Lidya; Anggraeni Sudiono Putri, Kartika (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
Consumptive behavior is a purchasing behavior that is no longer based on rational considerations. This study aims to analyze the influence of lifestyle and digital payments on bold consumptive behavior with self-control as a moderating variable. This study uses a quantitative research type and uses a descriptive approach. The location of the study was at UIN Maulana Malik Ibrahim Malang, for the population in this study all students of UIN Maulana Malik Ibrahim Malang who had shopped on the Shopee application with a digital payment system. This study uses a nonprobability sampling technique with a purposive sampling method with a sample size of 155 respondents. The data collection technique is by distributing questionnaires in a Google form. This study uses SEM PLS as a data analysis technique. This study found that lifestyle influences online consumptive behavior in UIN Maulana Malik Ibrahim Malang students who use the Shopee application, digital payments influence online consumptive behavior in UIN Maulana Malik Ibrahim Malang students who use the Shopee application, in addition, self-control cannot moderate between lifestyle and online consumptive behavior in UIN Maulana Malik Ibrahim Malang students who use the Shopee application, and self-control cannot moderate between digital payments and online consumptive behavior in UIN Maulana Malik Ibrahim Malang students who use the Shopee application.